Preparation for reuse activity of waste electrical and electronic equipment: Environmental performance, cost externality and job creation. (10th June 2019) - Pini, Martina; Lolli, Francesco; Balugani, Elia; Gamberini, Rita; Neri, Paolo; Rimini, Bianca; Ferrari, Anna Maria
Abstract: The European Waste Electrical and Electronic Equipment system introduced measures to encourage both the reduction of the amount of electronic waste and its separation to prepare for reuse. The aim of this study is compare the environmental performance, cost externality and job creation of the whole life cycle of new and reconditioned electrical and electronic equipment by adopting Life Cycle Assessment methodology. Five electrical and electronic equipment categories were investigated and the data collection was made on an Italian context. The refurbishing of breakdown electrical and electronic equipment was assessed by considering different sets of faulty components (Scenario A and B) and a total of 25 scenarios were studied. Moreover, both attributional and consequential life cycle inventory modelling framework were adopted to represent the investigated scenarios. The outcomes highlighted that the preparation for reuse process leads to obtaining a sustainable electronic device than the new one, depending on which set of components are replaced. Adopting Scenario B with the attributional model, the environmental damage of reconditioned electrical and electronic equipment decreases compared to the new one. Conversely, the consequential approach determines an environmental credit for all repaired electronic devices except for one category; in particular, Scenario A produced the largest environmental advantage. The analyses of external costs and social aspects confirm that the preparation for reuse activity allows to obtain a more sustainable product than a new one. For these two latter aspects, the results showed a turnaround passing from attributional model to consequential one. Noting the variability in results adopting both different life cycle inventory modelling framework and set of replaced components, the Life Cycle Assessment practitioner, that conducted the study, should help the decision-makers to determine which scenario is more sustainable accomplishing an adequate choice. Highlights: Sustainability comparison between the repaired electronic devices and the new ones. Environmental, jobs creation and external cost evaluations were carried out. Life Cycle Assessment methodology were adopted. "Preparation for reuse" could lead to obtaining a greener electronic device. The greenness of the reused electronic device depends on the components replaced.